Inhibiting the kynurenine pathway in spinal cord injury: Multiple therapeutic potentials? - Kelly R Jacobs; David B Lovejoy (Neural Regeneration Research, 2018)
Chronic induction of the kynurenine pathway (KP) contributes to neuroinflammation by producing the excitotoxin quinolinic acid (QUIN). This has led to significant interest in the development of inhibitors of this pathway, particularly in the context of neurodegenerative disease. However, acute spinal cord injury (SCI) also results in deleterious increases in QUIN, as secondary inflammatory processes mediated largely by infiltrating macrophages, become predominant. QUIN mediates significant neurotoxicity primarily by excitotoxic stimulation of the N-methyl-D-aspartate receptor, but other mechanisms of QUIN toxicity are known. More recent focus has assessed the contribution that neuroinflammation and modulations in the KP make in mood and psychiatric disorders with recent studies linking inflammation and modulations in the KP, to impaired cognitive performance and depressed mood in SCI patients. We hypothesize that these findings suggest that in SCI, inhibition of QUIN production and other metabolites, may have multiple therapeutic modalities and further studies investigating this are warranted. However, for central nervous system-based conditions, achieving good blood-brain-barrier permeability continues to be a limitation of current KP inhibitors.